Unlocking firm innovation under regional disadvantage : Can psychological openness compensate? - Grillitsch, Markus ; 0000-0002-8406-4727; Tavassoli, Sam; Obschonka, Martin (Research Policy, 2026)
Firm innovation is strongly shaped by regional endowment – defined here as regional supply- and demand-side conditions for innovation – yet many regions are disadvantaged by having low levels of such endowment. While recent research increasingly emphasizes the role of regional soft factors, such as psychological openness, we still know relatively little about how such factors influence firm innovation under conditions of low structural endowment. Theoretically, we draw on Schmookler's scissors metaphor to conceptualize regional supply and demand conditions as hard, structural endowments of regions. We argue that favorable regional soft conditions – specifically psychological openness – can partially offset these structural constraints, but only for firms that possess sufficient absorptive capacity to recognize, absorb, and exploit such favorable regional conditions. Using longitudinal firm-level data on Swedish firms from 2004 to 2018, we show that regional psychological openness does not have a universal positive effect on product innovation. Instead, our results indicate that the benefits of regional openness are concentrated among firms with higher absorptive capacity operating in regions with low endowment, while firms in regions with higher endowment do not benefit in the same way. Implications for research and policymaking are discussed.
Keywords: Firm endowments; Firm innovation; Low-endowment regions; Peripheral regions; Regional endowments; Regional psychological openness